Insulin Modulates the Immune Cell Phenotype in Pulmonary Allergic Inflammation and Increases Pulmonary Resistance in Diabetic Mice - Ferreira, Sabrina S.; Oliveira, Maria A.; Tsujita, Maristela; Nunes, Fernanda P. B.; Casagrande, Felipe B.; Gomes, Eliane; Russo, Momtchilo; Tavares de Lima, Wothan; Martins, Joilson O. (Frontiers in Immunology, 2020)
Introduction: Reports have shown that the onset of diabetes mellitus (DM) in patients previously diagnosed with asthma decreases asthmatic symptoms, whereas insulin aggravates asthma. The present study evaluated the modulatory effect of insulin on the development of allergic airway inflammation in diabetic mice. Materials and methods: To evaluate the effects of relative insulin deficiency, an experimental model of diabetes was induced by a single dose of alloxan (50 mg/kg, i.v.). After 10 days, the mice were sensitized with ovalbumin [OVA, 20 μg and 2 mg of Al(OH)3, i.p.]. A booster immunization was performed 6 days after the first sensitization [20 μg of OVA and 2 mg of Al(OH)3, i.p.]. The OVA challenge (1 mg/mL) was performed by daily nebulization for 7 days. Diabetic animals were treated with multiple doses of neutral protamine Hagedorn (NPH) before each challenge with OVA. The following parameters were measured 24 h after the last challenge: a) the levels of p38 MAP kinase, ERK 1/2 MAP kinases, JNK, STAT 3 and STAT 6 in lung homogenates; b) the serum profiles of immunoglobulins IgE and IgG1; c) the concentrations of cytokines (IL-4, IL-5, IL-10, IL-13, TNF-α, VEGF, TGF-β and IFN-γ) in lung homogenates; d) cells recovered from the bronchoalveolar lavage fluid (BALF); e) the profiles of immune cells in the bone marrow, lung, thymus, and spleen; and f) pulmonary mechanics using invasive (FlexiVent) and non-invasive (BUXCO) methods. Results: Compared to nondiabetic OVA-challenged mice, OVA-challenged diabetic animals showed decreases in ERK 1 (2-fold), ERK 2 (7-fold), JNK (phosphor-54) (3-fold), JNK/SAPK (9-fold), STAT3 (4-fold), the levels of immunoglobulins, including IgE (1-fold) and IgG1 (3-fold), cytokines, including Th2 profile cytokines such as IL-4 (2-fold), IL-5 (2-fold), IL-13 (4-fold), TNF-α (2-fold), VEGF (2-fold), and TGF-β (2-fold), inflammatory infiltrates (14-fold), T cells, NK cells, B cells and eosinophils in the bone marrow, lung, thymus and spleen, and airway hyperreactivity. STAT6 was absent, and no eosinophilia was observed in BALF. Insulin treatment restored all parameters. Conclusion: The data suggested that insulin modulates immune cell phenotypes and bronchial hyperresponsiveness in the development of allergic airway inflammation in diabetic mice.